Musandıralı evin tanımına dair notlar - Süslü, Nevsel Sezen (Omer Halisdemir Universitesi Muhendislik Bilimleri Dergisi, 2016)
There have been many interpretations about the description of type of house with musandira in Bodrum peninsula. Musandira, as an indoor element, has remarkable qualities. Although the houses are part of traditional architecture in Bodrum peninsula, they tend to disappear. For this reason, the previous researches on houses with musandira are also included in the study. Besides, as an example, a unique house in the peninsula is also included in the study. Keywords: Traditional architecture, traditional material, Bodrum, musandira, house with musandira
Keywords: Traditional architecture; traditional material; Bodrum; musandıra; house with musandıra; Geleneksel mimari; geleneksel malzeme; Bodrum; musandıra; musandıralı ev